Australia’s legislative response to the Basel Convention and the 2019 amendment to the convention: EN - Bradford, Emily; Grice, Matthew (ECOTON: Ecological Observation and Wetlands Conservation, 2021)
The Basel Convention is an international treaty which regulates the transboundary movement of hazardous waste across boarders, which impacts nations waste exportation and importation policies This paper discusses Australia’s implementation of the Basel Convention for the Control of Transboundary Movement of Hazardous Wastes and Their Disposal. By analysing legislation, academia and media pertaining to the topic this Article explores the history the Basel Convention for the Control of Transboundary Movement of Hazardous Wastes and Their Disposal, particularly emphasising the drafting process and the purpose of the legislation. Subsequently investigating Australia’s legislative implementation of its obligations. Ultimately this paper investigates Australia’s practices, with a particular emphasis placed on waste around Waste to Energy processes, against these obligations and the extent that Australia is upholding their obligations. This is done by exploring international trends away from plastic waste exportation the 2019 amendments of the Basel Convention. The article finds language used in the treaty impacts the ability to determine breaches of the treaty, however, notes various legislation that reinforce Australia’s commitment to the treaty. This is done without ruling out possible misconduct in the past.